Reflections on "Health Care in the Information Society - a Prognosis for the Year 2013" - Haux, Reinhold; Ammenwerth, Elske; Knaup-Gregori, Petra (Journal of medical systems, 2014)
In the year 2000 a talk was given and later published on how health care could look like in the year 2013. The aim was to “identify priorities in medical informatics research and necessary activities by policymakers in order to ensure an efficient, advanced, and yet affordable future health care system” (Haux R, Ammenwerth E, Herzog W, Knaup P. Health care in the information society. A prognosis for the year 2013. Int J Med Inform. 2002; 66: 3-21). In the year 2013 a workshop took place, critically reflecting on the prognoses and theses made for the year 2013. This editorial is reporting on the 2013-workshop and is introducing three papers, in which the workshop results have been summarized.